Nutritious underutilized species - Bambara groundnut - Alercia, A.; Bioversity International (2013)
Bambara groundnut is grown in Asia, parts of Northern Australia, and South and Central America and is widely distributed across the world. It is traditionally grown by women, giving it less value and less priority in land allocation, despite being regarded as the third most important legume in much of Africa after peanuts and cowpeas. Bambara groundnut is a neglected and underutilized species (NUS): a category of non-commodity cultivated and wild species, which are part of a large agricultural biodiversity portfolio today falling into disuse for a variety of agronomic, genetic, economic, social and cultural factors. NUS are traditionally grown by farmers in their centres of diversity, where they support nutrition security and other livelihood goals of local communities while contributing to meet their socio-cultural needs and traditional uses. Until recently these species have been largely ignored by research and development, becoming less competitive than well established major crops and losing gradually their diversity and associated traditional knowledge.